High-throughput methods to define complex stem cell niches. (April 2010) - Kobel, Stefan; Lutolf, Matthias P.
The potential of stem cells in clinics and as a diagnostic tool is still largely unmet, partially due to a lack of in vitro models that efficiently mimic the in vivo stem cell microenvironment—or niche—and thus would allow reproducible propagation of stem cells or their controlled differentiation in vitro. The current methodological challenges in studying and manipulating stem cells have spurred intense development and application of microfabrication and micropatterning technologies in stem cell biology. These approaches can be readily used to dissect the complex molecular interplay of stem cells and their niche and study single-cell behavior in high-throughput. Increased merging of microfabrication with advanced biomaterials technologies may ultimately result in functional artificial niches capable of recapitulating extrinsic stem cell regulation in vitro and on a single-cell level.